Pengembangan Bahan Ajar Matematika Berbasis Penemuan Terbimbing pada Pokok Bahasan Bangun Ruang Sisi Lengkung Kelas IX SMP/MTs - Rezky Amalia; Baharuddin; Sri Sulasteri; Nur, Fitriani; Sari, Agung Suci Dian (Alauddin Journal of Mathematics Education, 2023)
This study aims to develop and test the effectiveness of guided discovery-based mathematics teaching materials. The approach used is Research and Development (RnD) with the ADDIE development model. The test subjects in this study involved class IX students of SMPN 1 Sungguminasa. The research instrument used expert validation sheets, teacher and student response questionnaires, student activity observation sheets, and learning achievement tests. The results of this study indicate that the modules developed using the ADDIE development model consist of an analysis stage, a design stage, a development stage, an implementation stage, and an evaluation stage by producing an invention-based mathematics module. valid, practical, and effective guidance. The results of the validation from the experts stated that the average value of the guided discovery-based module aspect on the subject of curvature with a validity value of 4.5 was in the "very valid" category. The results of the teacher’s response questionnaire have a percentage of positive responses with an average of 87.5%. Then, it is known that the effectiveness of the module is 87.9% of students are in the complete category, the results of observations of student activity with an average of 57.1% are in the quite active category, and the average percentage of students’ positive responses is 93.9%. Thus, this study resulted in a guided discovery-based mathematics module that can be applied in learning.